Persepsi Mahasiswa Tentang Pemahaman Konsep Kinematika Gerak Ditinjau dari Kemampuan Berpikir Kritis - Puspitasari, Wahyu Dwi; Febrinita, Filda (UPEJ Unnes Physics Education Journal, 2020)
Motion kinematics is a subject mattern the Engineering Physics course that must be taken by students of the Computer Systems Study Program. The results of observations show that 30% of student learning outcomes are still below 75. This is the basis of research with the aim of knowing student perceptions of understanding the concept of motion kinematics so that lecturers can provide appropriate learning strategies in lectures. The research method used is qualitative with a phenomenological approach. The research subjects consisted of eight Computer Systems Study Program students who had taken engineering physics courses. The research instruments used were critical thinking skills test questions, test questions and concept understanding questionnaires, which had been validated by experts.The results showed that the students' perceptions of the Computer Systems study program on the concept of motion kinematics, which in terms of critical thinking skills showed, the average achievement of the translation indicator was 78%, the interpretation indicator was 75%, and the extrapolation indicator was 45%. The low achievement of extrapolation indicators shows that the ability of students to make conclusions from a problem is still lacking.